COMPARATIVE ANALYSIS OF PRICE AND PRODUCT QUALITY IN TRADITIONAL MARKETS AND TEMPORARY MARKETS IN BATU BARA - Fitrianingsih, Fitrianingsih; Mayastika Sinaga, Eka; Rahmawati, Dewi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
AbstractThis study aims to analyze the comparison of consumer behavior in terms of price and product quality in traditional and temporary markets. This type of research is a quantitative research with the number of respondents as many as 60 people with purposive sampling technique. Data analysis using SPSS. The results showed that either partially or simultaneously Price and product quality have a significant influence on consumer behavior in traditional and temporary markets. Furthermore, there is no difference in price and product quality on consumer behavior in traditional and temporary markets.